Gender Equality in Feminine Registers Used by Female Parents in Blitar: A Case Study of Local Wisdom of Addressing among Women with Respect to their Husbands’ Titles - Bagus Waluyo; Ali Mustofa (BRILIANT: Jurnal Riset dan Konseptual, 2021)
The theoretical framework used in the present form is Gender Construction in content analysis. The research observed two hundred selected female parents who have practiced mixed calling among male and female genders. The Data were collected using interviews and recordings carried out through online discussion during female parental activities of the home financial industry [PKK]. The analysis revealed that during the interaction among female parents, they addressed each other's name by mentioning their husbands' names for several reasons: 1) a lack of self-confidence which is influenced by their habits of always glorifying their husbands in all their activities, 2) Javanese culture in the city of Blitar still binds them, and It is complicated to get rid of it, 3) most of the mothers still have lower occupational education than their husbands, and 4) they are more respected by others if the husband's name is always attached to every activity.